The Influence Of Ewom At @Paimonfess On Purchase Intention Of Virtual Item On Genshin Impact In Indonesia - Pramasti, Galuh Sekar; Millanyani, Heppy; Giri, Refi Rifaldi Windya (eProceedings of Management, 2025)
The research background explores how game industries have evolved with free to play game model. Genshin Impact also has gained global attention with its gameplay. In-app purchases have become the main revenue of free to play game model. The big of online community and eWOM have led to the intention of purchasing in-game virtual items. The objective of this research is to measure how much eWOM influence the purchase intention of virtual item in Genshin Impact. This research adopts a quantitative approach by collecting data through surveys via a questionnaire from representative samples. This research found that mediating effects of eWOM Adoption on the influences of eWOM Usefulness and eWOM Credibility on Purchase Intention are all significant. Based on this result to increase the purchase intention of virtual item on Genshin Impact they need to utilizing the role of online community. In order to strengthen the eWOM of Genshin Impact.Keywords: Electronic Word of Mouth, eWOM, Purchase Intention, Virtual Item